Bioactivity of the Novel Fungicide SYP-14288 Against Plant Pathogens and the Study of its Mode of Action Based on Untargeted Metabolomics - Wang, Zhiwen (Plant disease, 2020)
Plant disease is a major threat to crop production, and fungicide application is one of the most effective methods to control plant disease. With emerging issues related to toxic residues and pathogen resistance, new fungicides with novel modes of action are urgently needed. SYP-14288 is a novel fungicide that could efficiently promote respiration and inhibit ATP biosynthesis in target organisms, but its bioactivity against various plant pathogens and exact mode of action are still unknown. In this study, we found that SYP-14288 is highly effective against 31 important plant pathogens belonging to a range of taxonomic groups. In addition, SYP-14288 has demonstrated excellent activity against all life stages of the important fungal plant pathogen Magnaporthe oryzae and is especially effective during the pathogen's high energy consumption stages. SYP-14288 showed good preventative control efficacy against pepper blight and rice blast in the greenhouse and field, respectively. In an untargeted metabolomics assay designed to determine the exact mode of action of SYP-14288, significant changes occurred in 25 metabolites, with the accumulation of seven fatty acid metabolites and a decrease in 18 starch and sugar metabolites (e.g., from the tricarboxylic acid cycle). This suggests that SYP-14288 is an uncoupling agent similar to 2,4-dinitrophenol, which can allow for accumulation of various fatty acids after destroying oxidative phosphorylation coupling, thereby inhibiting the growth of the phytopathogen. These results indicate that the novel uncoupler SYP-14288 is a promising agrochemical in plant disease management